Experimental and Modeling Density and Surface Tension of 1, 2-Dimethylbenzene with Alkanes at 298.15K - Andreatta, Alfonsina Ester (2016)
Experimental density and surface tension of 1,2-dimethylbenzene with octane, nonane and decane have been obtained at 298.15K and atmospheric pressure. This work increases the available experimental information regarding this kind of mixtures useful in the fuel field. The excess molar volume and the surface tension deviation have been correlated by Redlich-Kister polynomial equation. Besides, density of binary systems has been predicted and correlated with Nitta-Chao group contribution and ERAS models respectively while the surface tension deviation have been predicted with HSIS and HSEG and SE models. Finally, a comparison about the behavior of excess volume molar and deviation surface tension between dimethylbenzene isomers and alkanes is presented.